Clinical management of urolithiasis - Knoll, Thomas; Pearle, Margaret S. (Springer Berlin / Heidelberg, 2012)
With the incidence of urolithiasis rising worldwide, this vital addition to the literature is a practical guide for urologists on the diagnosis, management, and prevention of urinary calculi, ranging from new imaging procedures to interventional treatments.